Alcohol versus dry umbilical cord care among newborn infants in occupied Palestinian territory: a controlled trial. (August 2017) - Shahrour, Maher; Sawalha, Nour AlHuda; Masri, Murad; Rajabi, Hanan; Eddin, Mohammad Salah; Jo'beh, Taha; Shalabi, Sundus; Lafi, Ala'; Jawabra, Ebtihal; Khreim, Waseem; Natsheh, Sa'eed; Awwad, Motee Abu; et al.
Abstract: Background: Omphalitis is considered a leading cause of sepsis among newborn infants and topical antiseptic cord care is usually recommended. In 2003, WHO recommended the use of dry cord care in settings where the risk of omphalitis and sepsis is low. In Palestine, recommendations on umbilical cord care are not clear; the 70% alcohol cord care method is still used as standard by many and the chlorhexidene method is virtually unknown. In this study we compared the alcohol and dry cord care methods among healthy newborns in two urban hospitals in the occupied Palestine territory. Methods: A non-randomised controlled trial was conducted in the newborn nurseries of two tertiary hospitals in East Jerusalem and Hebron. Newborn infants born at 37 or more weeks' gestation between March and October, 2014, were enrolled. Infants with major congenital anomalies who were admitted to neonatal intensive care unit, required antibiotics at birth, or had a hospital stay of more than 72 h, were excluded. One group of parents was asked to clean the infant's stump with 70% alcohol, and the other group to use dry cord care, changing methods on a weekly basis. The study was approved by the ethics committees of both hospitals. Written consent was obtained from participating parents. Findings: 692 newborn babies were enrolled to both treatment groups. 344 used dry cord care and 348 the alcohol cord care method. No infants developed cord infection. The mean time to separation of the umbilical cord was 7·03 days (SD 2·47) in the dry cord care group and 8·13 days (2·47) in the alcohol cord care group (p<0·001). Interpretation: Our findings suggest that dry cord care is safe, is associated with a reduced separation time, and can be recommended for use in our context. Neither method of cord care was associated with the development of omphalitis in any of the study participants. A limitation of our study was that randomisation was impossible in view of the work overload and limited human resources at our hospitals. Funding: None.